Peramalan Jumlah Barang Kereta Api di Indonesia Menggunakan Metode Seasonal Autoregressive Integrated Moving Average (SARIMA) - Syahzaqi, Idrus; Sediono, Sediono; Oktavia, Sabrina Salsa; Anggakusuma, Aurellia Calista; Wieldyanisa, Ezha Easyfa (Jurnal Statistika dan Komputasi, 2025)
Background: Freight transportation is an important part of the business run by PT Kereta Api Indonesia. To support effective strategic planning and infrastructure development, an accurate prediction of the amount of goods to be transported in the future is required. Therefore, historical data-based forecasting methods such as Seasonal Autoregressive Interated Moving Average (SARIMA) can be a relevant approach to predict the number of railway goods in Indonesia. Objective: Obtain a suitable model to forecast the number of goods transported by rail transportation in Indonesia, and to determine the results of the forecasting. Methods: This research uses the time series method with the Seasonal Autoregressive Integrated Moving Averang (SARIMA) model approach based on data characteristics that show seasonal patterns. SARIMA itself is able to integrate seasonal pattern components in the data and is able to effectively capture periodic and structural dynamics in seasonal data. Results: The best model obtained is probabilistic SARIMA(0,1,1)(0,1,1)12, using secondary data sourced from the Central Bureau of Statistics (BPS) in the range of January 2013 to March 2024. Forecasting for the next 12 months (April 2023 to March 2024) shows a Mean Absolute Percentage Error (MAPE) value of 8.03% which indicates that the level of forecasting accuracy is very good. Conclusion: The probabilistic ARIMA(0,1,1)(0,1,1)12 model can be used as a reliable reference in predicting the amount of goods transported through rail transportation in Indonesia.